Modelling socio-economic dynamics in a working class desegregation area in post-industrial, post-Apartheid South Africa : the case of Danville-Elandspoort, Pretoria - Horn, A.C. (Andre Carl) (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2008.